2020
DOI: 10.1101/2020.10.16.341925
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Pre-meiotic, 21-nucleotide Reproductive PhasiRNAs Emerged in Seed Plants and Diversified in Flowering Plants

Abstract: Plant small RNAs (sRNAs) are important regulatory elements that fine-tune gene expression and maintain genome integrity by silencing transposons. They have critical roles in most pathways involved in plant growth and reproductive development. Reproductive organs of monocots produce abundant phased, small interfering RNAs (phasiRNAs). The 21-nt reproductive phasiRNAs triggered by miR2118 are highly enriched in pre-meiotic anthers, and have not been described in eudicots. The 24-nt reproductive phasiRNAs are tri… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
32
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
1

Relationship

4
1

Authors

Journals

citations
Cited by 11 publications
(32 citation statements)
references
References 47 publications
0
32
0
Order By: Relevance
“…Out of the 11 clusters, six are polycistronic precursors; Figure 1B shows an example of a polycistronic cluster. To study 24-nt phasiRNA expression in columbine, we analyzed sRNAs data derived from vegetative tissues (leaf and root) and reproductive tissues (four unopened bud stages; Pokhrel et al, 2020). We found that mature miR2275 sequences highly accumulate in bud stages two and three (Figure 1C) which represent meiotic/post-meiotic stages of anther development.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Out of the 11 clusters, six are polycistronic precursors; Figure 1B shows an example of a polycistronic cluster. To study 24-nt phasiRNA expression in columbine, we analyzed sRNAs data derived from vegetative tissues (leaf and root) and reproductive tissues (four unopened bud stages; Pokhrel et al, 2020). We found that mature miR2275 sequences highly accumulate in bud stages two and three (Figure 1C) which represent meiotic/post-meiotic stages of anther development.…”
Section: Resultsmentioning
confidence: 99%
“…In the genome browser, it is apparent that the first 24-nt phasiRNAs are generated from the cleavage site of aco_can81 and miR2118 (Figure 2E and 2F), respectively. Interestingly, members of both of these miRNA families also trigger production of 21-nt reproductive phasiRNAs in columbine (Pokhrel et al, 2020).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations